Development and Release of High Yielding Clones of Eucalyptus tereticornis SM. - Kumar, Ashok; Savita; Ginwal, H. S.; Dobhal, Shivani; Sharma, Shruti; Shrivastava, Priyanka; Rana, Anchal; Kumar, Rahul (Indian Forester, 2017)
Eucalyptus, a native of Australia, is one of the most favoured exotic species used under various plantation programme world over. In India, it is cultivated in about 8 million ha under various climatic conditions. The growing stock and yield in eucalypt plantations varies considerably, and therefore it was utmost essential to raise large scale plantations with improved planting stocks. Based on field performance, three clones were recommended for commercial cultivation in northern India. The productivity of recommended clones varied from 14.68 (FRI-ET-32) to 23.04 (FRI-ET-31) m3 ha-1 yr-1, with an average of 19.44 m3 ha-1 yr-1, which records to about 76% superiority to evaluated genotypes and checks. Most importantly, two of these selected clones were derived from Burdekin River, Queensland, Australia, and one is a unique collection from the FRI Estate. In this way, depleting diversity levels of Indian eucalypts could well be enriched to a substantial level by infusing such newer clones and used for enhancing productivity of Eucalyptus plantations as well.